Symptomatic Onset of Severe Hemophilia A in Childhood is Dependent on the Presence of Prothrombotic Risk Factors - Escuriola Ettingshausen, C.; Halimeh, S.; Kurnik, K.; Schobess, R.; Wermes, C.; Junker, R.; Kreuz, W.; Pollmann, H.; Nowak-Göttl, U. (Thrombosis and Haemostasis, 2001)
It has been recently suggested that the clinical phenotype of severe hemophilia A (HA) is influenced by co-inheritance with the factor V G1691A mutation. We therefore investigated 124 pediatric PUP patients with hemophilia (A: n = 111) consecutively admitted to German pediatric hemophilia treatment centers. In addition to factor VIII activity, the factor V (FV) G1691A mutation, the prothrombin (PT) G20210A variant, antithrombin, protein C, protein S and anti-thrombin were investigated. 92 out of 111 HA patients (F VIII activity < 1%) were suffering from severe HA. The prevalence of prothrombotic risk factors in children with severe HA was no different from previously reported data: FV G1691A 6.5%, PT G20201A 3.2%, and protein C type I deficiency 1.1%. No deficiency states of antithrombin or protein S were found in this cohort of hemophilic patients. The first symptomatic bleeding leading to diagnosis of severe hemophilia (< 1%) occurred with a median (range) age of 1.6 years (0.5-7.1) in children carrying defects within the protein C pathway or the PT gene mutation compared with non-carriers of prothrombotic risk factors (0.9 years (0.1-4.0; p = 0.01). The cumulative event-free bleeding survival was significantly prolonged in children carrying additionally prothrombotic defects (log-rank/Mantel-Cox: p = 0.0098). In conclusion, data of this multicenter cohort study clearly demonstrate that the first symptomatic bleeding onset in children with severe HA carrying prothrombotic risk factors is significantly later in life than in non-carriers.
Keywords: Severe hemophilia A; pediatric PUP patients; factor V G1691A; prothrombin G20210A